PENGARUH PROGRAM MEMBERSHIP, DISKON, DAN KEPUASAN KONSUMEN TERHADAP LOYALITAS KONSUMEN DI TOSERBA LINTANG SHOP BOJONG - Siswi Pertiwi, Dita; Arifiyanto, Muhammad (Penerbit Lafadz Jaya, 2026)
The fokus of this study is to examine the influence of membership programs, price discounts, and customer satisfaction on customer loyalty at Toserba Lintang Shop Bojong. The study used a quantitative method with probability sampling through simple random sampling, resulting in 85 respondents who had made purchases. Data was colled using an online questionnaire (Google Form) and analyzed using multiple linear regression with help of SPSS. The results of the analysis show that individually, membership programs, price discounts, and customer satisfaction have a positive and significant contribution to customer loyalty, with price discounts being the most dominant factor. Simultaneously, these three variables also had a significant effect on customer loyalty, as indicated by the coefficient of determination (R²) value of 0.809 This means that 80.9% of the changes in customer loyalty were explained by the model, while the remaining 19.1% were influenced by factors outside the scope of the study. These findings reveal that customer retention strategies in local retail need to integrate the provision of economic incentives through discounts, strengthen the benefits of membership programs, and continuously improve customer satisfaction in order to build long-term customer loyalty.